Narrating of collaborative governance in Sejarah Beach restoration, Batu Bara Regency, Indonesia - Gunawan, Tedi (Department of Government Studies, Universitas Muhammadiyah Makassar, 2024)
This article examines the collaborative governance strategy implemented by the Batu Bara Regency Government in restoring Sejarah Beach. Beaches are critical assets that represent the identity of a region, provide economic benefits, and support the surrounding environmental ecosystem. Unfortunately, many beaches experience environmental degradation and other socio-economic problems. Pantai Sejarah in Batu Bara Regency is no exception, which faces issues such as prostitution, environmental degradation, and local poverty. Using a qualitative methodology, this research explores the collaborative approach used in the revitalization of Pantai Sejarah. In-depth interviews were conducted with various key stakeholders, including representatives from local government agencies (Environmental Agency, Forestry Agency, and Regional Development Agency), PT Inalum's HR management, and local community members. The findings of this study show that the implementation of the collaborative governance approach by the local government has transformed Sejarah Beach into an integrated tourist attraction. In addition, this collaborative initiative also created economic opportunities, including small businesses, new jobs, and revenue for the government. The collaborative effort also addresses social issues such as prostitution through coordinated action between law enforcement, government, and the local community. Furthermore, the collaborative governance approach provides a comprehensive solution to coastal area management by addressing social challenges alongside environmental conservation and economic development.